Efektivitas Layanan Bimbingan Klasikal dengan Metode Diskusi untuk Meningkatkan Motivasi Belajar Siswa - Rifqi, Hany Muhammad; Handayani, Arri; Ajie, Gergorius Rohastono (Universitas PGRI Semarang, 2024)
The problem that will be raised in this study is whether there is an effective classical guidance service with the discussion method to increase student motivation at SMA N 3 Pati. Based on the problem formulation, the purpose of this study was to find out how effective the discussion method classical guidance service was to increase student motivation at SMA N 3 Pati. This type of research is experimental. This research method uses a true experimental design with a posttest-only control design technique. The population in this study is class XI MIPA 1, XI MIPA 2, XI MIPA 3, XI MIPA 4, XI MIPA 5, XI MIPA 6, XI MIPA 7, XI MIPA 8, XI MIPA 9, XI IPS 1, XI IPS 2, and XI IPS 3 with a total of 377 students. The sample in this study was selected randomly which was then divided into 2 classes, namely XI MIPA 4 experimental class and XI MIPA 5 control class. The sampling used is cluster random sampling. The results of this research analysis revealed that the independent sample test test obtained post-test data with a value of sig, 0.006 0.05, which means that there is a difference in the increase in student motivation to learn in the group given treatment or treatment through classical guidance services with the discussion method.